This is my Body ...: A Lutheran perspective on the Eucharist, digitalization, mediality, and presence - Deeg, Alexander (Dansk Teologisk Tidsskrift, 2022)
In times of the Covid-19 pandemic, many congregations had to stop celebrating the Eucharist or find new ways to do so – one of these being online Eucharist services in synchronous and diachronous settings. The article describes developments in the Protestant Churches of Germany and shows that the interplay of theology and church practices is essential. On the background of the fundamental dialectics of absence and presence in (Christian) liturgy and Luther’s writings on the Lord’s Supper, the article proposes two axes that open up a ‘field’ of diverse ritual practices: community and gift. Many different ways of celebrating the Lord’s Supper seem to be possible in this field – also celebrations in synchronous digital settings (video conferences). The Covid-19 crisis is seen as a chance to rethink sacramental theology and ways of celebration – in the context of a permanent change of liturgical practices.